Strengthening the Content of Local History in Social Studies - Erlina Wiyanarti; Ersis Warmansyah Abbas; Syaharuddin Syaharuddin; Jumriani Jumriani; Mutiani Mutiani; Muhammad Rezky Noor Handy (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2023)
This study aims to analyze the importance of incorporating local content in teaching materials and provide relevant examples. A comprehensive analysis of the existing literature was conducted to describe the research findings. The study results depict the content related to the lives of Indonesian people during the Islamic period, addressing essential competencies. The findings also highlight the necessity for additional material descriptions and examples derived from local and regional history. Social studies learning can be further developed by reinforcing social studies teaching materials with local content. Therefore, local historical sources from Banjar are incorporated into social studies learning materials used in the classroom. These include the establishment of the Banjar Sultanate, the kings of Banjar, and the development of Banjar culture. The selection of the Banjar Sultanate as local content is based on its alignment with the periodization in Indonesian history.